Efeitos da urbanização sobre a dieta e seleção de presas por Poecilia reticulata em riachos da bacia do rio Paraná, Brasil. - Ganassin, Maria Julia Mileo (2016)
This study investigated if the diet and selection of preys by Poecilia reticulata, Peters, 1859 can reflect the environmental conditions in streams. The soil Impervious Surface (IS) total area was used as a metric measure. The sub-basin streams of Pirapó and Paraná rivers (PR) were classified as rural and urban ones, respectively, those with a low BIS and a high percentage of soil impervious surface (AIS). It was evaluated the hypothesis that both, diet and selectivity, differ between BIS and AIS stream groups, and among the hydrological periods, especially in AIS streams. Macroinvertebrates accounted for 90% of the species diet, regardless the stream and period. Concerning diet and prey selection there were differences between BIS and AIS streams groups, however, when considering the hydrological period, significant differences were observed only for AIS streams. In BIS streams, the food spectrum was wider (16 types of prey) and there was a selection of more preferential preys: Cladocera, Copepoda, Lepidoptera, Empididae, Muscidae and Simuliidae in the rain, in addition to Cladocera, Copepoda, Amphipoda, Chironomidae, Muscidae and Simuliidae during drought. Considering the AIS streams, the species has shown a low diet in relation to the items (12), and there was a high dominance of a single type of prey (Chironomidae), which was also reflected in the lower food selectivity. The following preys were selected in these streams: Lepidoptera, Chironomidae and Simuliidae in the rain, in addition to Collembola and Ceratopogonidae during drought. Ephemeroptera and Trichoptera were always avoided, regardless the stream and period, whereas Coleoptera and Oligochaeta were avoided only in BIS and AIS streams, respectively. The results showed that diet and prey selection by P. reticulata have been changed and might reflect the environmental conditions in streams when using the IS as an explanatory variable.